2020
DOI: 10.48550/arxiv.2005.06257
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tensor product categorifications, Verma modules and the blob 2-category

Abstract: We construct a dg-enhancement of Webster's tensor product algebras that categorifies the tensor product of a universal sl 2 Verma module and several integrable irreducible modules. We show that the blob algebra acts via endofunctors on derived categories of such dg-enhanced algebras in the case when the integrable modules are twodimensional. This action intertwines with the categorical action of sl 2 . From the above we derive a categorification of the blob algebra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…They also showed in [37] that their construction is related to Khovanov-Rozansky triply-graded link homology [26]. Moreover, in a collaboration [27] with Lacabanne, they gave a categorification of the tensor product of a Verma module with multiple integrable modules for quantum sl 2 . They also showed that their construction yields a categorification of the blob algebra of Martin-Saleur [32], which allow the construction of invariants of tangles in the annulus.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…They also showed in [37] that their construction is related to Khovanov-Rozansky triply-graded link homology [26]. Moreover, in a collaboration [27] with Lacabanne, they gave a categorification of the tensor product of a Verma module with multiple integrable modules for quantum sl 2 . They also showed that their construction yields a categorification of the blob algebra of Martin-Saleur [32], which allow the construction of invariants of tangles in the annulus.…”
Section: Introductionmentioning
confidence: 94%
“…Before defining the dgKLRW algebras, we fix some conventions, and we recall some common facts about dg-structures (classical references for this are [19] and [44], see also [34, Appendix A] for a short survey oriented towards categorification), and about rewriting methods. Since we use the same conventions as in [27], a part of this section is almost identical to [27, §3.1 and Appendix B].…”
Section: Preliminaries and Conventionsmentioning
confidence: 99%
See 3 more Smart Citations